Anxiety Influence on the development of temporomandibular disorders - Mylene María Rodríguez-Betancourt; Ileana María Yero-Mier; Jorge Luis de Castro-Yero; Camilo Adrián Fernández-Rodríguez; Bárbara Yudelky Dorta-Capita (Revista Información Científica, 2022)
Introduction: the temporomandibular disorders constitute an important health problem in Cuba. Today, it´s well known that the psychosocial factors play an important role in it, especially, with regard to pain adaptation and recovery.